A mathematical model to investigate on the thermal performance of a flat plate solar air collector and its experimental verification. (1st May 2016) - Sun, Chuan; Liu, Yuting; Duan, Chen; Zheng, Yao; Chang, Huawei; Shu, Shuiming
Highlights: A mathematical model is proposed for flat plate solar air collector. All components of the solar air collector are modeled separately in detail. Indoor experiments are conducted to verify the accuracy of this mathematical model. Optimum mass flow rates for solar air collector under different conditions are found. Abstract: A mathematical model based on numerical finite-difference approach under forced convection mode was presented for the SAC. Airflow channel, absorber plate, glass cover, thermal insulation board and fan power were taken into consideration in this model and analyzed in detail. In order to verify the accuracy of this model, an indoor experimental system was built to study the performance of a double pass flow SAC. The effect of the inlet mass flow rate of the collector on the thermal performance was investigated under various environmental conditions. The outlet air temperature obtained from the theoretical and experimental studies are in reasonable agreement, which supports the validity of the theoretical model. By considering the energy gained and the fan power consumed under real conditions, the optimum mass flow rates were discussed and simulated with different ambient temperature and solar irradiance, which showed that for this flat plate SAC, m ̇ opt equals 0.03 kg/s at I = 400 W/m 2, equals 0.04 kg/s at I = 700 W/m 2, and equals 0.045 kg/s at I = 1000 W/m 2 . The results are useful for analyzing and designing new SACs.